(untitled) (Al-Aasar, 2025)
This article offers a critical analysis of Quranic verse 65:4 (Surah At-Talaq). This verse has often been cited in debates about the permissibility of child marriage in Islam. Traditional exegetical readings have interpreted the verse as legitimizing the divorce and remarriage of prepubescent girls (al-saghīrah), drawing on certain hadith reports that claim the Prophet’s marriage to Āʾishah at the age of six and consummated at nine. This study challenges such interpretations by conducting a close linguistic and contextual examination of the verse, alongside related Qur’anic passages such as 4:1–4, 4:6, 4:19, among others. The analysis demonstrates that the language of verse 65:4 does not support its application to prepubescent girls, and that interpretations to this effect reflect cultural and political overlays rather than the Qur’an’s intended meaning. Instead, the Qur’an consistently frames marriage as a contractual union requiring maturity, consent, and accountability, thereby excluding the possibility of child marriage. Hadith reports that appear to endorse early marriage are considered only as part of the broader exegetical discourse but are shown to be secondary and methodologically less reliable when weighed against the Qu’ran’s primary guidance. The article concludes that Qur’an 65:4, properly understood, does not sanction child marriage. Rather, it reinforces the Qu’an’s overarching vision of marriage as a bond between responsible individuals, while early marriage practices should be understood as remnants of pre-Islamic cultural traditions not Qura’nic prescriptions.